0695 The Association Between Social Support at Work and Sleep Quality - Shurovi, Sumayya; David, Michelle; Sedano, Brandon Fernandez; Cornelius, Talea; Schwartz, Joseph; Abdalla, Marwah (Sleep (New York, N.Y.), 2023)
Introduction Social support, including support received by coworkers, is associated with one’s emotional well-being. Poor sleep quality among employees is associated with worse employee health, increased workplace injury and is a growing occupational health problem. Social support at home is known to positively impact sleep quality. However, whether social support at work affects sleep quality is unknown. We examined whether social support at work is associated with sleep quality. Methods The Worksite Blood Pressure study is a multi-site study of psychological factors and ambulatory blood pressure. The study recruited 472 participants without major cardiovascular disease from 10 New York City worksites during 4 waves over 11 years. The current analysis was restricted to 189 employed participants at Wave 4 and provided complete data. Participants completed the Job Content Questionnaire which assessed psychosocial and social characteristics of jobs, including social support received from coworkers and supervisors, and a sleep questionnaire. The sleep questionnaire assessed sleep quality, self-reported sleep duration, alertness, and sleep habits. For this analysis, items related to sleep quality were summed. Higher scores indicated worse sleep quality. A linear regression model was specified predicting sleep quality from social support at work. Study site, age, race/ethnicity, marital status, total number of people at home, and years of education were included as covariates. Results Of the 189 participants, 72.5% were male, 16.4% were Black, 7.4% were Hispanic/Latinx, and 73.0% were married. Mean age was 50.1 years (SD = 7.0), mean years of education was 17.8 (SD = 3.2), and median number of people at home was 3 (Range 0, 6). Mean support at work was 23.3 (SD = 3.9) and mean sleep quality was 8.6 (SD = 4.4). Social support at work was not significantly associated with sleep quality, B = 0.12, 95% CI -0.29, 0.05, p = 0.16. Sensitivity analyses that examined support from supervisors and from coworkers separately were also not significant, p > 0.20. Conclusion Social support at work was not significantly associated with sleep quality in our cohort. Factors beyond social support at work should be investigated to evaluate their associations with employees’ sleep quality. Support (if any) P01HL47540